Literature Review : Penyakit Degeneratif : Penyebab, Akibat, Pencegahan Dan Penanggulangan - Fatihaturahmi Fatihaturahmi; Yuliana Yuliana; Asmar Yulastri (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Degenerative diseases are generally defined as diseases caused by a process of decreased organ function which generally occurs in old age. This disease has many varieties and symptoms and often attacks the community in general. In Indonesia, the epidemiological transition has led to a shift in disease patterns, in which there has been an increase in degenerative diseases. Degenerative disease is a chronic non-communicable disease due to the decline in the function of the body's organs due to the aging process. Indonesia's health sector is currently bearing a double burden, because on the one hand there has been an increase in degenerative diseases, while on the other hand infectious diseases are still rampant. Purpose: to gain a better understanding of problems related to degenerative diseases: causes, effects, prevention and management. Method: In this study we used a research method in the form of library research, which is a series of studies relating to library data collection methods, or the research was collected through various kinds of library information (scientific journals, books, encyclopedias, magazines, newspapers, and documents). Conclusion: Based on the research results obtained from reviewing journals that match the theme, it can be concluded that the poor and middle class are more at risk of death from degenerative diseases ENMD and DCS than the rich. While the population with the age group of 45–54 years is more at risk of dying from DCS degenerative disease than those aged 33 years.